#TITLE_ALTERNATIVE# - BRILIANTO GAUTAMA (NIM : 12909005), FERNANDUS
This study aims to analyze the relation between physical-chemical of water quality and the growth rate of Vannamei shrimp (Litopanaeus vannamei) during seasional variation. The water quality data (temperature, salinity, pH, DO, ammonia, ammonium, nitrite and nitrate) and the weight of a shrimp were taken at Balai Pengembangan Budidaya Air Payau dan Laut (BPBAPL) Karawang since April 2012 until July 2013. The water quality parameter for optimum range growth of Vannamei shrimp are pH (7,4 - 8,9), and ammonia (0,02 Ã‚Â– 0,08 mg/l). Variations of temperature (25,6 - 30,40C), salinity (3 - 29 ppt), and DO (2,2 - 4,7 mg/l) are below optimum range for the growth of Vannamei shrimp. Variations of ammonium (0,02 - 10,5 mg/l), nitrite (0,02 - 5 mg/l) and nitrate (0,03 - 50 mg/l) are above optimum range for the growth of Vannamei Shrimp. The correlation of water quality parameter that have strong relation with the growth rate of Vannamei shrimp are salinity, with the correlation value r at - 0,302 which have signification of 95%. From the graphical analysis, strong relationship is occurred between DO and the growth rate of vannamei. If the DO value increases, the growth rate of vannamei is increased as well. The result shows that maximum growth rate of Vannamei shrimp is occurred at pond H2 which is observed during West Monsoon (January - March 2013), presented as 0,29 gram/day. Therefore, the suitability of pH, DO, ammonia, ammonium, nitrite and nitrate and its optimum range is observed.